2019
DOI: 10.3727/096504018x15424939990246
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of lncRNA PVT1 Inhibits Glioma Progression by Regulating miR-424 Expression

Abstract: Plasmacytoma variability translocation 1 (PVT1), an oncogene, has been reported to be highly expressed in many tumors, including human glioma, gastric cancer, and non-small cell lung cancer. Functionally, it could also regulate the development of tumor cells. However, its specific roles and pathogenesis in human gliomas are still not clear. This study investigated the function and mechanism of PVT1 knockdown in the proliferation and malignant transformation of human gliomas. We first examined the expression le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…Our results imply that silencing of miR-424-5p abolishes the suppression effects on glioma proliferation, migration, and invasion caused by ropivacaine. In agreement with a previous study [ 30 ], our results suggest that miR-424-5p has a carcinoma suppressor role in the development of glioma. Similar results were also documented in cervical and renal cancers, whereby miR-424 exerted its tumor inhibitor roles by impeding cell growth and increasing apoptosis [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our results imply that silencing of miR-424-5p abolishes the suppression effects on glioma proliferation, migration, and invasion caused by ropivacaine. In agreement with a previous study [ 30 ], our results suggest that miR-424-5p has a carcinoma suppressor role in the development of glioma. Similar results were also documented in cervical and renal cancers, whereby miR-424 exerted its tumor inhibitor roles by impeding cell growth and increasing apoptosis [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 93%
“…Cell cycle arrest and apoptosis can be induced by either silencing PVT1 or overexpressing miR-195 in osteosarcoma (20). In cervical cancer and glioma, PVT1 improves tumor growth by negatively regulating miR-424 (21, 22). Similar mechanisms have been reported for PVT1-miR-146a, PVT1-miR-497, PVT1-miR-26b, and PVT1-miR-133a (10, 2326).…”
Section: Mechanismsmentioning
confidence: 99%
“…Several studies, including investigations of large datasets (115), found higher PVT1 expression in glioma tissue and cell lines than normal (116)(117)(118)(119)(120).…”
Section: Overview -Expression Patternmentioning
confidence: 99%